The Influence Mechanism of Interaction Quality in Live Streaming Shopping on Consumers’ Impulsive Purchase Intention - Li, Guangming; Jiang, Yue; Chang, Liting (Frontiers in Psychology, 2022)
As a new mode of online shopping, live streaming shopping has the characteristics of high interactivity. Live streaming shopping has achieved many positive results, but it leads to the phenomenon of consumers' impulsive purchase. To analyze the reasons for the impulsive purchase intention , we can not only make up for the lack of attention paid to this issue, but guide related enterprises and anchors to carry out marketing activities and consumers to rational consumption It can promote the sustainable development of the live streaming industry. Therefore, combined with cognitive evaluation theory, the research is carried out from the perspective of interaction quality, to explore the influence mechanism of interaction quality between anchors and consumers on consumers' emotions and impulsive purchase intention. Data were collected through questionnaires and tested using hierarchical regression methods. The test results show that: responsiveness, professionalism, informedness and personalization have a significantly positive impact on consumers' arousal and pleasant emotion; Consumers' emotion have a significantly positive impact on their impulsive purchase intention; Consumers' extroverted personality significantly negatively moderates the relationship between professionalism and informedness and consumers’ arousal and pleasure emotion.